Competition and Efficiency in Banking : Behavioral Evidence from Ghana - Mathisen, Johan (IMF Working Papers; Working Paper ;, 2005)
This paper assesses the degree of bank competition and discusses efficiency with regard to banks' financial intermediation in Ghana. By applying panel data to variables derived from a theoretical model, we find evidence for a noncompetitive market structure in the Ghanaian banking system, which may be hampering financial intermediation. We argue that the structure, as well as the other market characteristics, constitutes an indirect barrier to entry thereby shielding the large profits in the Ghanaian banking system.